Analytical Profile of Punarnavadi Ghrita- An Ayurvedic Formulation - Arya T; Shiji R S (International Journal of Ayurveda and Pharma Research, 2024)
Punarnavadi Ghrita, a traditional Ayurvedic formulation, is used in the management of Madatyaya (alcoholism). It comprises Punarnava (Boerhaavia diffusa), Yashtimadhu (Glycyrrhiza glabra), Godugdha (cow's milk), and Goghrita (cow's ghee). The present study focuses on the analysis of this Ghrita as per the general guidelines for drug development of Ayurvedic formulations. This formulation was prepared following the general procedure of Bhaishajya Kalpana, ensuring the authenticity and quality of raw ingredients through rigorous organoleptic assessment. Physicochemical analyses were conducted to determine parameters such as optical rotation, iodine value, saponification value, specific gravity, and free fatty acid content. Phytochemical screening revealed the presence of alkaloids, phenols, and terpenoids. HPTLC analysis at 254nm and 366nm wavelengths identified multiple peaks, indicating a complex profile of active compounds. Heavy metal, pesticide residue, and microbial contamination tests confirmed the safety of the formulation, with no harmful contaminants detected. The findings offer a comprehensive profile of Punarnavadi Ghrita, establishing quality benchmarks for its therapeutic use and providing a reference standard for future research. This study underscores the formulation's potential in replenish Ojadhatu and mitigate the adverse effects of alcoholism, aligning with ancient Ayurvedic wisdom.